Determination of puberty based on morphometric measurements and the gonadosomatic index of lovebird (Agapornis fischeri) testes - Nabila Chusnannada; Yeni Dhamayanti; Boedi Setiawan; Sunaryo Hadi Warsito; Tri Wahyu Suprayogi; Kuncoro Puguh Santoso (Universitas Airlangga, 2026)
This study aimed to determine the relationship between age and testicular morphometrics in lovebird (Agapornis fischeri), as well as the relationship between age and the gonadosomatic index (GSI) of the testes, and to evaluate the effect of body weight on testicular weight in determining the onset of puberty. This study used 30 lovebirds divided into three age groups: 4, 5, and 6 months, with ten birds in each group. The variables measured were testicular length, width, volume, weight and body weight. Data were analyzed using correlation analysis, simple linier regression, and paired sample t-test. The results showed a positive relationship between age and testicular length, width and volume. The GSI values of lovebirds aged 4, 5 and 6 months were 0.015 ± 0.002, 0.058 ± 0.011, and 0.400 ± 0.067, respectively, indicating an increase with age. The significance coefficient at 4 months of age was 0.000 (p <0.05), indicating that body weight had a significant influence on testicular weight at this age. In contrast, lovebirds aged 5 and 6 months had significance coefficients of 0.079 and 0.089 (p >0.05), indicating that testicular weight was not significantly influenced by body weight at these ages. It can be concluded that lovebirds at 6 months of age are likely to have reached puberty.